COMPETITIVENESS OF SMALL AND MIDDLE BUSINESS AS A SIGNIFICANT ELEMENT OF REGIONAL ECONOMY DEVELOPMENT - Petrova, Anastasiya; Aznabaeva, Gulmariam; Mineeva, Vera; Ismagilova, Tagira; Iraeva, Nadezhda (Revista Inclusiones, 2020)
The article considers the modern economic situation in the Russian Federation, in particular, the degree of small and middle businesses development under reforms taking place at the verge of the 2020-s. The authors analyzed the scientific literature on the topic, devoted to the theoreticalmethodological foundations and practical issues of developing the competitive advantages of business entities. Also, the authors analyzed the works of scientific-practical conferences, legislative and normative documents of the Russian Federation and the Russian regions in the sphere of support and development of business activity. Due attention is paid to the Order of the Russian President No. 596 of 7 May 2012 “On long-term state economic policy”, which stipulates the need to take appropriate measures to increase the position of the Russian Federation in the World Bank ranking on doing business from the 35th to the 20th position in 2018. The possibilities of small and middle businesses, which are flexible and capable of fast adaptation to the new forms of competition, have significantly increased. An attendant factor of increasing the number of small and middle businesses is their active participation in integrative relations. To study the aspect of the small and middle business integration in more detail, the authors consider the “integration” doctrine as one of the key forces, driving the development of modern economy at all levels (international, national, regional, municipal). Appropriate attention is paid to diversification of the global economy, which resulted in substantia reforms in international relations entailing changes in all spheres of the country’s economy (political, social, etc.). The research methodology is the analysis of dynamics of business entities development, based on statistical data. The authors conclude that, under destabilization of the global economy, the Russian government assigns an important role to small and middle business entities, more adaptable for the constantly changing market situation due to their flexibility.